Age of bronze (1998), volume 3b ebook Betrayal pt 2. - Shanower, Eric (Age of Bronze (1998), 2018)
The Trojan plain fills with death as Achaean forces clash in blood with the Trojan army. In the city of Troy Pandarus pulls the strings to put Troilus in Cressida's bed. But when Cressida is ripped away to the enemy camp, how far will Troilus fight to recover her? Collects AGE OF BRONZE #27-33.. Author: Eric Shanower. Illustrator: Eric Shanower . 2013 Eric Shanower.